Origin of Dolomite in Lacustrine Organic-Rich Shale: A Case Study in the Shahejie Formation of the Dongying Sag, Bohai Bay Basin - Zhao, Ziru; Dong, Chunmei; Ma, Pengjie; Lin, Chengyan; Li, Guiang; Du, Xinyu; Luan, Guoqiang; He, Yinjun; Liu, Weibin (Frontiers in Earth Science, 2022)
In most organic-rich shale reservoirs, dolomite is widely distributed and has different types and crystal sizes. However, the characteristics and formation mechanism of the dolomites in organic-rich shale are still poorly understood. Petrographic and geochemical analyses were performed to interpret the formation of dolomite in the lacustrine organic-rich shale of the Shahejie Formation, Dongying Sag, Bohai Bay Basin. Four types of dolomites, which represent episodic recrystallization, were classified based on crystal size and shape: 1) micritic dolomite (Dol-1), 2) sub-to euhedral (cloudy cores with clear rims) dolomite (planar-e) (Dol-2), 3) anhedral dolomite (coarse planar-s to nonplanar crystals) in phosphatic particles (Dol-3), and 4) fracture-filling anhedral dolomite (Dol-4). Dol-1 has nonplanar mosaic micritic crystals with irregular intercrystalline boundaries and dull cathodoluminescence (CL), suggesting dolomitization during the early burial stage. Dol-1 tends to occur under high paleosalinity and warm conditions. Furthermore, the syngenetic relationship, with abundant framboidal pyrite and gypsum, suggests that bacterial sulfate reduction (BSR) may influence the formation of Dol-1. The high content of Sr and low content of Mn/Sr also indicate less influence on burial. The Dol-2 crystals show cloudy cores with clear rims attributed to progressive dolomitization during burial. Dol-2 is always associated with the organic matter within the organic matter-rich lamina. The anhedral crystals and undulate (sweeping) extinction of Dol-3, which is usually encased by phosphatic particles in the organic-rich lamina, reflect the recrystallization affected by bacteria and the subsequent thermal evolution of organic matter. Dol-4 fulfills the abnormal pressure fractures crosscutting the earlier phases (Dol-1 and Dol-2) with undulate (sweeping) extinction and different rare earth element (REE) patterns. Dol-4 may be affected by hydrothermal fluids, which are influenced by the thermal evolution of organic matter. The 87Sr/86Sr values of the four types of dolomites similarly demonstrate the same dolomitizing fluids. Dol-1 to Dol-3 have similar REE patterns but are different from Dol-4, suggesting that Dol-4 likely resulted from circulation through basinal sediments instead of different fluids. Focusing on the origin of dolomite has been instrumental in understanding the diagenetic evolution, fluid flow, and organic-inorganic interactions in organic-rich shale and, hence, the reservoir formation of shale oil.